Multiarmed spiral waves generated by periodic stimuli in excitable systems. (July 2020) - Luengviriya, Jiraporn; Sutthiopad, Malee; Kanchanawarin, Jarin; Luengviriya, Chaiya
Abstract: Rotating spiral waves occur in different excitable systems. They also play an important role in the human health since the spiral waves of electrical signals correspond to some cardiac arrhythmia like tachycardia and fibrillations. Pinning of a spiral wave is found to stabilize extreme conditions such as the superconductivity and the superfluidity and it also causes longer cardiac arrhythmia. Multiarmed spiral waves are multiple spiral arms rotating in the same direction around a common center. In heart, they are expected to be seriously dangerous since the wave frequency increases with the number of spiral arms. In this article, we present a partition method with periodic stimuli to generate multiarmed spiral waves pinned to a circular obstacle. Periodic stimuli applied on one side of a thin line partition ignite multiple waves with large distances between them so only a few wave fronts can be distributed around the obstacle and subsequently result in multiarmed spiral waves with a few arms after the removal of the partition. In contrast, Periodic stimuli on both two sides of the partition create waves with smaller distances between them and more wave fronts can fit around the obstacle boundary. Therefore, multiarmed spiral waves with more arms can be generated using the latter method.